A meta-analysis of the effects of acupuncture on limb function, depression and quality of life in stroke patients (针灸对卒中患者肢体功能、抑郁症状和生活质量影响的Meta分析) - LEI Hong (雷宏); SUN Xinyu (孙新雨); LANG Yanru (郎艳茹); YIN Anchun (尹安春) (中西医结合护理)
Objective To evaluate the effects of acupuncture on physical function, depression and quality of life in stroke patients. Methods A systematic search of the publicly available databases such as the Cochrane Library, PubMed, Embase, China Knowledge Network (CNKI), Wan Fang Data, VIP Database (VIP) and China Biomedical Literature Database (CBM) was conducted, and randomized controlled trials on the use of acupuncture in stroke patients from its inception to April 10, 2023 were included for the Meta analysis. Results Thirteen studies were included. The results showed that acupuncture could promoted recovery of limb function ［MD=6. 86, 95%CI (5. 63, 8. 08), P＜0. 01］, improved depressive symptoms common in post-stroke patients ［MD=-6. 95, 95%CI (-9. 32, -4. 57), P＜0. 01］, and improved patients' quality of life ［SMD=1. 83, 95%CI (1. 63, 2. 04), P＜0. 01］. Conclusion Acupuncture can not only promote the recovery of limb function, but also improve depressive symptoms common in post-stroke patients and enhance their quality of life. (目的 评价针灸对卒中患者肢体功能、抑郁症状和生活质量的干预效果。方法 系统检索the Cochrane Library、Pub Med、Embase、中国知网(CNKI)、万方数据库(Wan Fang Data)、维普数据库(VIP)和中国生物医学文献数据库(CBM)从建库至2023年4月10日公开发表的关于针灸应用于卒中患者的随机对照试验。结果 最终纳入13篇文献。结果表明, 针灸在促进患者肢体功能的恢复［MD=6. 86, 95%CI(5. 63, 8. 08), P＜0. 01］, 改善卒中后患者常见的抑郁症状［MD=-6. 95, 95%CI(-9. 32, -4. 57), P＜0. 01］, 提升患者生活质量［SMD=1. 83, 95%CI(1. 63, 2. 04), P＜0. 01］方面优于对照组。结论 针灸不仅可以促进患者肢体功能的恢复, 而且可以改善卒中后患者常见的抑郁症状, 提升患者生活质量。)